DiLight: Digital light table – Inbetweening for 2D animations using guidelines. (June 2017) - Carvalho, Leonardo; Marroquim, Ricardo; Vital Brazil, Emilio
Highlights: A semi-automatic inbetweening method is proposed, where guideline information is used to aid the animation production. A virtual light table helps the artist to infer inbetween movements before drawing the final art. A layer hierarchy strategy is used to deal with occlusions and complex animations. Regions can be defined and interpolated for producing colored and filled animations. Abstract: In traditional 2D animation several intermediate frames are drawn between two consecutive key frames. This process can be very time-consuming and tedious for the animator. In this paper we present a semi-automatic inbetweening method that is tightly coupled with the animation production pipeline. We exploit the fact that artists typically start with an outline of the drawing to help preview the illustration, and use these guidelines to improve the curve correspondence inference. The method is based on a two-level matching algorithm, where the first one finds correspondences between the guidelines, and the second one between the final art. This separation further aids the artist by using transformed guidelines and drawings from preceding frames to guide the creation of new ones, acting as a digital light table. We show the robustness of our method with a variety of animation examples, including sequences from animation books and professional animators. Graphical abstract: